From Cattle to Beef Onscreen: Animal Rendering as Extraction in Industrial Livestock Films - Benjamín Schultz-Figueroa (Media + Environment)
This essay sets out to ask what happens if we consider the raising, killing, and distribution of livestock animals as a form of extraction alongside other more recognizable forms such as mining or logging. It focuses on a series of livestock films made by the agriculture industry during the 1940s and 1950s, including *Cattle Country* (Elizabeth Zinkan, 1944), *Know Your Meat* (John R. Humphreys, 1945), *Cattle and the Cornbelt* (Leo Seltzer, 1949), and *Herds West* (Avalon Daggett, 1955), among others. I argue that the procedure described by Nicole Shukin as "animal rendering," in which animal bodies are processed into both useable commodities and powerful images, is a crucial component of so-called "extractive media." Through close analysis of how factory farming films set out to transform living, breathing animals into both lively images of American agriculture and dead bodies on a massive scale, I demonstrate how, even in this overdetermined context, the material specificity of documentary film contains indexical links to the original animals and thus allows the films to contain meanings beyond those intended by their industrial creators.